The Pawnee Ghost Dance Hand Game A Study of Cultural Change - Lesser, Alexander (Columbia University Contributions to Anthropology, 1933)
Studies the history of the Pawnee from the very early 1800's.  Looks specifically at the complexities of the ghost dance and the hand game and maintaining the essential values of the Native American culture